The Impact of Cigarette Advertisements on Adolescents : A Literature Review (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2019)
Cigarette consumption occurs throughout the world and is widespread among teenagers. Moreover, the existence of cigarette advertisements as a promotional media that is easily found in various mass media, can provide smoking influences to adolescents. The purpose of this study was to determine the effects of cigarette advertising on adolescent smoking initiation. This study uses a literature review. Google Scholar, Sciene Direct, and Proquest are used to select literature related to the topic to be discussed. The analysis in this study was also assisted with several articles found on the internet. Based on research, the influence of various types of cigarette advertisements in general in various countries can lead to smoking initiation among adolescents. The image in cigarette advertisements makes smokers look attractive. Teenagers who are exposed to cigarette advertisements are more open and have a high curiosity about the use of cigarettes. Some actions need to be taken to reduce cigarette consumption in adolescents, such as providing cigarette education to adolescents, as well as enforcement of strong anti-smoking advertising, promotion and sponsorship policies. So, the teenagers know and understand the harmful effects of using these cigarettes. Keywords: Cigarette advertisement, adolescent health, smoking.